2022
DOI: 10.3389/fmicb.2022.797234
|View full text |Cite
|
Sign up to set email alerts
|

Time Is of the Essence—Early Activation of the Mevalonate Pathway in Apple Challenged With Gray Mold Correlates With Reduced Susceptibility During Postharvest Storage

Abstract: Apple is typically stored under low temperature and controlled atmospheric conditions to ensure a year round supply of high quality fruit for the consumer. During storage, losses in quality and quantity occur due to spoilage by postharvest pathogens. One important postharvest pathogen of apple is Botrytis cinerea. The fungus is a broad host necrotroph with a large arsenal of infection strategies able to infect over 1,400 different plant species. We studied the apple-B. cinerea interaction to get a better under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In apple (Malus × domestica Borkh. ), a recent study observed extensive transcriptome reprogramming upon inoculation, with 28.9% of expressed genes showing significant differential regulation, and the early activation of the mevalonate pathway correlates with reduced susceptibility, leading to smaller lesion diameters [36].…”
Section: Discussionmentioning
confidence: 96%
“…In apple (Malus × domestica Borkh. ), a recent study observed extensive transcriptome reprogramming upon inoculation, with 28.9% of expressed genes showing significant differential regulation, and the early activation of the mevalonate pathway correlates with reduced susceptibility, leading to smaller lesion diameters [36].…”
Section: Discussionmentioning
confidence: 96%
“…These include simple hydrocarbon terpenes and terpenoids or isoprenoids that are produced via the activation of the cytosolic MVA pathway. Naets et al [53] showed a strong negative correlation between the upregulation of MVA pathway at early time points with the success of B. cinerea infection. From the current study, we identify that all the transcripts involved in the MVA pathway were up-regulated and support the fact that terpenoids are key for plant defense.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, the terpenoid accumulation and the transcript levels of the underlying pathway genes revealed differences between LSL and SSL, with MEP pathway being clearly stimulated in SSL, and MVA pathway more activated in LSL ( Figure 6 ). Previously, the early transcriptional stimulation of MVA pathway that produces the building blocks for terpenoids, was correlated with reduced susceptibility of apples during postharvest storage ( Roberto et al., 2022 ). Key up-regulated genes in the case of SSL included DXS , DXR , and HDS of MEP pathway, whereas in the case of LSL, two out of the three HMGR transcripts (MVA pathway).…”
Section: Discussionmentioning
confidence: 99%